2018
DOI: 10.1016/j.ejps.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated poly(anhydride) nanoparticles for oral delivery of docetaxel

Abstract: The aim of this work was to investigate the potential of pegylated poly(anhydride) nanoparticles to enhance the oral bioavailability of docetaxel (DTX). Nanoparticles were prepared after the incubation between the copolymer of methyl vinyl ether and maleic anhydride (Gantrez® AN), poly(ethylene glycol) (PEG2000 or PEG6000) and docetaxel (DTX). The oral administration of a single dose of pegylated nanoparticles to mice provided sustained and prolonged therapeutic plasma levels of docetaxel for up 48-72 h. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In particular, it is reported that PMVE/MA can be structured as loadable nanoparticles [9] and its derivates poly(methyl vinyl ether-alt-maleic acid) (PMVE/MA-Ac) and poly(methyl vinyl ether-alt-maleic monoethyl ester) (PMVE/MA-Es) as nanofibers [10,11]. In addition, these polymers have shown utility as matrix elements, allowing the combination with other materials to generate novel mixtures of chemical properties in the final nanostructures [11][12][13], such as with homemade fluorescent cationic fluorene-based polyelectrolytes [11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is reported that PMVE/MA can be structured as loadable nanoparticles [9] and its derivates poly(methyl vinyl ether-alt-maleic acid) (PMVE/MA-Ac) and poly(methyl vinyl ether-alt-maleic monoethyl ester) (PMVE/MA-Es) as nanofibers [10,11]. In addition, these polymers have shown utility as matrix elements, allowing the combination with other materials to generate novel mixtures of chemical properties in the final nanostructures [11][12][13], such as with homemade fluorescent cationic fluorene-based polyelectrolytes [11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterial-based carriers have been widely studied as transport vehicles for various substances, such as drugs, due to their ability to increase local accessibility to the target and enhance bioavailability [1,2,3,4]. It is important to select a suitable nanoparticle (NP) for the fabrication of a nanocarrier as well as a ligand, which will be immobilized on the NP, to capture and release the target drug.…”
Section: Introductionmentioning
confidence: 99%
“…GAN is a biocompatible polymer (25) that contains a high concentration of carboxylic acid groups in its structure ( Figure 1). The combination of GAN with molecules containing alcohol groups via an esterification reaction has been used in the past to prepare different types of materials for biomedical applications (26)(27)(28)(29). In the present work GAN was crosslinked using PEG.…”
Section: Hydrogel Synthesis and Characterisationmentioning
confidence: 99%